2009
DOI: 10.1007/s11832-009-0179-4
|View full text |Cite
|
Sign up to set email alerts
|

Leg muscle atrophy in idiopathic congenital clubfoot: Is it primitive or acquired?

Abstract: To investigate whether atrophy of the leg muscles present in congenital clubfoot (CCF) is primitive or secondary to treatment of the deformity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 38 publications
4
59
0
2
Order By: Relevance
“…We showed that leg muscle atrophy is a primitive defect in congenital clubfoot rather than a consequence of treatment, in agreement with previous pathologic observations in foetuses and stillborns with congenital clubfoot [2][3][4][5][6][7][8]. We also showed that leg muscle atrophy increases with the patient's age, and, therefore, a mechanism of muscle growth impairment was suggested as a possible pathogenetic factor of congenital clubfoot [1].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We showed that leg muscle atrophy is a primitive defect in congenital clubfoot rather than a consequence of treatment, in agreement with previous pathologic observations in foetuses and stillborns with congenital clubfoot [2][3][4][5][6][7][8]. We also showed that leg muscle atrophy increases with the patient's age, and, therefore, a mechanism of muscle growth impairment was suggested as a possible pathogenetic factor of congenital clubfoot [1].…”
Section: Discussionsupporting
confidence: 90%
“…In a previous histologic and MRI study on UCCF [1], we measured the leg muscle surface on either histologic crosssections of foetus legs or MRI cross-scans of the legs of untreated newborns and treated children and adults. We showed that leg muscle atrophy is a primitive defect in congenital clubfoot rather than a consequence of treatment, in agreement with previous pathologic observations in foetuses and stillborns with congenital clubfoot [2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…49 There is inconsistent evidence that the incidence of clubfoot was associated with historical seasonal outbreaks of poliomyelitis. 57 with the authors hypothesising that clubfoot may be the result of a muscle growth impairment.…”
Section: Pre-natal Influencesmentioning
confidence: 99%
“…113 Intrinsic factors such as the absence of major arteries of the foot, peripheral neuropathy and the altered histology of musculature and ligaments seen in some cases of clubfoot may contribute to the pathophysiology of relapse. [56][57][58]61,62 It is widely acknowledged that after initial correction most clubfeet in families who are noncompliant with an appropriate bracing regime will experience a structural relapse.…”
Section: Aetiology Of Relapsementioning
confidence: 99%
“…1 The Achilles tendon acts as an invertor 2 and the calf muscles are shortened. 3 ITEV, more commonly known as clubfoot, is a disorder affecting one or both lower limbs with fifty percent of cases being bilateral.…”
mentioning
confidence: 99%